Learning Engagement Effect on Satisfaction, and Future Preferences of Online Tax Brevet - Agustina, Karina Dwi; Saragih, Arfah Habib (Dinamika Pendidikan, 2022)
This study investigates the factors that influence student satisfaction with online tax brevet and their preferences in the future, using theory of perceived user satisfaction. There have been several studies examining tax education, but research on technology-based tax education is still difficult to find. Using an online survey distributed in August – September 2021, data were collected from 106 participants who have or are currently taking online tax brevet. The data is then processed by the PLS-SEM method. This study found that technology and course had a significant effect on student satisfaction, on the other hand, teacher, communication, Covid-19 impact, and sudden change did not have a significant effect. On student involvement, it was found that only motivation had a significant effect, while self-efficacy and anxiety had no significant effect. In this study, student involvement was also indicated to have a significant effect on student satisfaction and learning outcomes. Student satisfaction itself also has an influence on student decisions in the future to continue using online tax brevet technology. To maintain the future preferences of students, tax brevet organizers can increase student motivation with a more interactive learning system.